Pathology and genetic connectedness of the mangrove crab (Aratus pisonii) – a foundation for understanding mangrove disease ecology - Bojko, Jamie; Burgess, Amy L.; Allain, Thomas W.; Ross, Erica P.; Pharo, Devon; Kreuze, Jan F.; Behringer, Donald C. (Animal diseases, 2022)
Mangrove forests are productive ecosystems, acting as a sink for CO 2 , a habitat for a diverse array of terrestrial and marine species, and as a natural barrier to coastline erosion. The species that reside within mangrove ecosystems have important roles to play, including litter decomposition and the recycling of nutrients. Crustacea are important detritivores in such ecosystems and understanding their limitations (i.e. disease) is an important endeavour when considering the larger ecological services provided. Histology and metagenomics were used to identify viral ( Nudiviridae , Alphaflexiviridae ), bacterial ( Paracoccus sp., ' Candidatus Gracilibacteria sp.’, and Pseudoalteromonas sp.), protozoan, fungal, and metazoan diversity that compose the symbiome of the mangrove crab, Aratus pisonii . The symbiotic groups were observed at varying prevalence under histology: nudivirus (6.5%), putative gut epithelial virus (3.2%), ciliated protozoa (35.5%), gonad fungus (3.2%), gill ectoparasitic metazoan (6.5%). Metagenomic analysis of one specimen exhibiting a nudivirus infection provided the complete host mitochondrial genome (15,642 bp), nudivirus genome (108,981 bp), and the genome of a Cassava common mosaic virus isolate (6387 bp). Our phylogenetic analyses group the novel nudivirus with the Gammanudivirus and protein similarity searches indicate that Carcinus maenas nudivrius is the most similar to the new isolate. The mitochondrial genome were used to mine short fragments used in population genetic studies to gauge an idea of diversity in this host species across the USA, Caribbean, and central and southern America. This study report several new symbionts based on their pathology, taxonomy, and genomics (where available) and discuss what effect they may have on the crab population. The role of mangrove crabs from a OneHealth perspective were explored, since their pathobiome includes cassava-infecting viruses. Finally, given that this species is abundant in mangrove forests and now boasts a well-described pathogen profile, we posit that A. pisonii is a valuable model system for understanding mangrove disease ecology.